Description and Evaluation of the Implementation of a Weight-Based, Nurse-Driven Heparin Nomogram in a Tertiary Academic Medical Center. (March 2018) - Schurr, James W; Stevens, Craig A; Bane, Anne; Luppi, Carol; Culbreth, Sarah E.; Miller, Amy Leigh; Connors, Jean M.; Sylvester, Katelyn W.
Weight-based, nurse-driven heparin nomograms are reported in the medical literature to improve the time it takes to reach a minimum threshold for anticoagulation without compromising patient safety in specific indications or patient populations. This is the first report in the literature of an institution-wide protocol implementation and evaluation of effectiveness with simultaneous transition to an electronic health record. The purpose of implementing this practice change at our institution was to standardize practice, improve time to reach therapeutic anticoagulation, and improve patient safety. We conducted a retrospective analysis utilizing a pre/postimplementation design to compare outcomes. The primary end point evaluated was the time to reach minimum threshold value for therapeutic anticoagulation. Additionally, we assessed the percentage of patients who reached minimum threshold therapeutic anticoagulation within 24 hours, the percentage of patients with a critically supratherapeutic activated partial thromboplastin time (aPTT) value (≥120 seconds) during therapy, and a description of heparin titration for the first 4 aPTT results with nomogram use. Overall time to therapeutic anticoagulation decreased from a mean 18.7 to 11.7 hours (hazard ratio [HR] 1.59; 95% confidence interval 1.22-2.08; P < .0005). Percentage of patients receiving therapeutic anticoagulation within 24 hours increased from 74.4 to 88.5 (odds ratio [OR 2.97, P = .002) and the percentage of patients with an aPTT ≥120 seconds remained constant at 49.9 versus 46.8 (OR 0.92, P = .73). This practice change reduced time to therapeutic anticoagulation without an increase in the proportion of patients with a critically supratherapeutic aPTT at our institution.